IMPLEMENTASI PROGRAM PENANGANAN KEKERASAN SEKSUAL TERHADAP ANAK DI KECAMATAN BINJAI KABUPATEN LANGKAT (Studi DI Dinas PPKB Dan PPA Kabupaten Langkat) - Aginta Agustina Br Ginting Suka; Ti Aisyah; Maryam, Maryam (Bajang Institute, 2024)
One of the efforts of the Langkat Regency government in addressing sexual violence against children is the implementation of Regional Regulation Number 3 of 2022 concerning Child-Friendly Regency Policy, which is carried out by the Population Control Family Planning and Women's Empowerment and Child Protection Office of Langkat Regency. However, in implementing this policy, the office faces challenges. Therefore, the purpose of this research is to assess the implementation of Langkat Regency government's policy in addressing sexual violence against children and the obstacles faced by the Population Control Family Planning and Women's Empowerment and Child Protection Office of Langkat Regency. The research utilizes a qualitative descriptive approach supported by secondary data, including primary data from interviews and secondary data from observations. Data analysis involves collecting informant information through interviews and concluding findings. The research findings indicate that the Population Control Family Planning and Women's Empowerment and Child Protection Office of Langkat Regency has implemented Regional Regulation Number 3 of 2022, but faces obstacles such as lack of community understanding of sexual violence against children and many people being unaware of the duties and functions of the office